Lipases secreted by a gut bacterium inhibit arbovirus transmission in mosquitoes. - Xi Yu; Liangqin Tong; Liming Zhang; Yun Yang; Xiaoping Xiao; Yibin Zhu; Penghua Wang; Gong Cheng (PLoS Pathogens)
Arboviruses are etiological agents of various severe human diseases that place a tremendous burden on global public health and the economy; compounding this issue is the fact that effective prophylactics and therapeutics are lacking for most arboviruses. Herein, we identified 2 bacterial lipases secreted by a Chromobacterium bacterium isolated from Aedes aegypti midgut, Chromobacterium antiviral effector-1 (CbAE-1) and CbAE-2, with broad-spectrum virucidal activity against mosquito-borne viruses, such as dengue virus (DENV), Zika virus (ZIKV), Japanese encephalitis virus (JEV), yellow fever virus (YFV) and Sindbis virus (SINV). The CbAEs potently blocked viral infection in the extracellular milieu through their lipase activity. Mechanistic studies showed that this lipase activity directly disrupted the viral envelope structure, thus inactivating infectivity. A mutation in the lipase motif of CbAE-1 fully abrogated the virucidal ability. Furthermore, CbAEs also exert lipase-dependent entomopathogenic activity in mosquitoes. The anti-arboviral and entomopathogenic properties of CbAEs render them potential candidates for the development of novel transmission control strategies against vector-borne diseases.